2009
DOI: 10.25249/0375-7536.2009393519532
|View full text |Cite
|
Sign up to set email alerts
|

Geotermobarometria de granulitos do Cinturão Ribeira na porção norte do estado do Rio de Janeiro: seção Italva (RJ) – Patrocínio do Muriaé (MG)

Abstract: Resumo Este trabalho apresenta um estudo sobre as condições metamórficas de um segmento do Cinturão Ribeira no norte do Estado do Rio de Janeiro, com base em cálculos de pressão e temperatura em granulitos e gnaisses com granada na seção Italva (RJ) -Patrocínio do Muriaé (MG). Os granulitos localizados a oeste de Itaperuna (RJ) apresentam intervalos de temperatura entre 754 e 775°C e de pressão entre 7,9 e 8,6 kbar, enquanto os granulitos localizados a leste de Itaperuna mostraram valores de 702 a 722°C e de 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…Litotipo/localização P (Kbar) T (°C) Santos et al (2005) Gnaisses da região de São Fidélis, no centro norte fluminense 8-9 750-800 Marques (2009) Metapelitos do Domínio Cambuci no norte fluminense 6,62 718 Marques (2009) Metabasitos do Domínio Cambuci em Bom Jesus do Itabapoana (RJ) 6,9 ± 1,9 720 Karniol et al (2009) Granulitos entre Patrocínio do Muriaé e Itaperuna 7,9 e 8,6 754-775 Karniol et al (2009) Granulitos entre Itaperuna e Italva 8,0 e 9,1 702-722 Marques et al (2017) Metabasitos do Domínio Cambuci em Bom Jesus do Itabapoana 10,5 850…”
Section: Autorunclassified
“…Litotipo/localização P (Kbar) T (°C) Santos et al (2005) Gnaisses da região de São Fidélis, no centro norte fluminense 8-9 750-800 Marques (2009) Metapelitos do Domínio Cambuci no norte fluminense 6,62 718 Marques (2009) Metabasitos do Domínio Cambuci em Bom Jesus do Itabapoana (RJ) 6,9 ± 1,9 720 Karniol et al (2009) Granulitos entre Patrocínio do Muriaé e Itaperuna 7,9 e 8,6 754-775 Karniol et al (2009) Granulitos entre Itaperuna e Italva 8,0 e 9,1 702-722 Marques et al (2017) Metabasitos do Domínio Cambuci em Bom Jesus do Itabapoana 10,5 850…”
Section: Autorunclassified
“…In a regional context, some authors obtained geothermobarometer data for the Araçuaí-Ribeira Orogen System, which can be related with Oriental Terrane and Central Superterrane of Ribeira Belt and support the data in the present study. Karniol et al (2009) analyzed granulites located west of Itaperuna (RJ) with temperature ranging between 754 and 775 °C and pressure ranging between 7.9 and 8.6 kbar and granulites located east of Itaperuna with temperature values from 702 to 722 °C and pressure values from 8.0 to 9.1 kbar. Relatively lower temperatures and pressures, between 50 to 100 ºC and between 2.0 to 3.0 kbar, were obtained for the aluminous gneisses that emerge between Itaperuna and Italva.…”
Section: Discussionmentioning
confidence: 99%
“…As evidenced by the morphology of the zircon grains and high Th/U ratios, the high metamorphic grade of the rocks is also evidenced by mineral peak metamorphic associations typical of the granulite facies (with orthopyroxene + clinopyroxene + plagioclase) in all study samples. The Neoproterozoic granulite metamorphism is common in the entire JFC (Duarte et al 1997, Heilbron et al 1998, Medeiros Júnior et al 2017) and is also observed in nearby units, such as the paragneisses from the Raposos and Bom Jesus do Itabapoana groups and in the orthogneisses from the Neoproterozoic Serra da Bolivia/Rio Doce magmatic arc (Karniol et al 2009, Santos et al 2011, Gouvêa et al 2020, Marques et al 2021). In addition, the observation of hornblende and biotite partially substituting orthopyroxene and clinopyroxene in some samples suggests retrometamorphism in conditions of upper amphibolite facies, also in agreement with regional works (Santos et al 2011, Ferreira et al 2020, Marques et al 2021.…”
Section: Neoproterozoic Metamorphic Overprintmentioning
confidence: 97%